(untitled) (Research, Society and Development, 2022)
To analyze the results achieved in hospital performance indicators with the implementation of the Kanban system for bed management in a reference maternity hospital in high-risk pregnancy. Retrospective and cross-sectional research with a quantitative approach. Carried out in a teaching maternity hospital in Teresina - PI, a tertiary reference for maternal and child care. Secondary data collected in the period before and after the implementation of the Kanban system was used, between the months of January to December 2017 and the months of January to December 2018. The tests of Chi-square, Kolmogorov-Smirnov and Mann-Whitney U non-parametric test with the aid of the Software Statistical Package for Social Sciences considering the 95% confidence interval. There was an increase in maternal hospitalizations and discharges after the implementation of Kanban in the maternity where there were 7122 admissions (48.8%) and 7472 (51.2%) in 2017 and 2018, respectively. Regarding discharges, there are 5132 (46.7%) and 5854 (53.3%) in the years studied. With regard to an occupancy rate, there was a decline from 95.63% to 93.7% in the years studied. Meanwhile, the Average Length of Stay had a decrease from 9.12 to 8.08 days and the turnover rate increased from 4.32 to 4.83%. Using hospital indicators allows managers, managers and health professionals to have a broad view of the main complications related to bed turnover and the flow and supply of services. It is concluded that the Kanban technology was able to contribute to improve the management of necessary beds among professionals, encouraging proactive cooperation in the hospitalization flow and improving clinical quality in the maternity hospital.